De-Autonomy of Post-Human Imagination: New Directions in the Theory of Art - Stepanov, Mikhail A. (Actual Problems of Theory and History of Art, 2022)
The article is devoted to the problem of interpretation of new media art. It is proposed to consider the new phenomena of art through the concepts of de-autonomy and posthuman imagination. De-autonomy is affirmed as an essential feature of a work of contemporary art. This concept captures the fundamental “non-autonomy” of the existence of art, the situational nature of actions, the interdependence of contexts, the interpenetration and interconnection of environments.The embodiment of digital reality objects in the physical environment, both screen images and paintings, installations, sculptures and other complex objects, requires an updated theoretical approach. The interconnection of a complex ecosystem of constant material transformation of objects becomes obvious. Man has “delegated” many abilities to machines, including “intelligence” — neural networks. The camera’s gaze is no longer tied to the subject’s point of view. It is the gaze, but the gaze of an “object” that internalizes into our own subjectivity, becoming our vision, so much so that no overseer is required to maintain this system. This is the process of developing of a posthuman imagination.Posthuman imagination is based on corporeality, which has the experience of interacting with the emerging techno-genic visuality and digital materiality, when the experience of thinking machines becomes a human aesthetic experience.
Keywords: de-autonomy; posthuman imagination; posthuman studies; media; artificial intelligence; relations; digital art; new media art; non-human subjectivity; aesthetics of experience